Averaging principle for 1D stochastic Landau-Lifshitz-Bloch equation - Jiang-lun Wu (Chinese Quarterly Journal on Pure and Applied Mathematics, 2022)
In this paper, we study the strong averaging principle for 1D stochastic Landau-LifshitzBloch equation (SLLBE). The averaging principle is an effective method for studying the qualitativeanalysis of nonlinear dynamical systems. Under some assumptions, utilising Khasminkii′s time discretisation approach, we show the solution of SLLBE can be approximated by the solutions to averaged stochastic systems in the sense of mean square.